1976
DOI: 10.1128/jvi.18.3.1120-1130.1976
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the oncornavirus particles in the plasma of guinea pigs with L2C leukemia

Abstract: The inoculation of L2C guinea pig leukemia cells into strain 2 guinea pigs results in the death of the animals within 12 to 15 days. Death is preceded by the simultaneous appearance in the plasma of (i) elevated leukocyte levels, (ii) extracellular virus particles, and (iii) a particle-associated RNA-directed DNA polymerase. This enzyme activity has a cation preference identical to that of the type B bromodeoxyuridine-induced guinea pig virus, i.e., an Mg2+ optimum at 20 mM and no activity using Mn2. Competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Using competition hybridization, Michalides et al (18) reported the homology between the genome of BUdR-induced GPV and virus particles in the plasma pellet of L2C leukemic guinea pigs. However, two types of particles were found in leukemic plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using competition hybridization, Michalides et al (18) reported the homology between the genome of BUdR-induced GPV and virus particles in the plasma pellet of L2C leukemic guinea pigs. However, two types of particles were found in leukemic plasma.…”
Section: Resultsmentioning
confidence: 99%
“…However, experiments using radiolabeled probes (cDNA or vRNA) from purified particles found in leukemic plasma and leukemic lymphoblasts will be necessary to determine whether viruslike particles observed in leukemic lymphoblasts and leukemic plasma are identical to BUdR-induced GPV. We and others have found the preparation of such probes difficult, using either leukemic plasma (18) or leukemic cells (24).…”
Section: Resultsmentioning
confidence: 99%